Jaringan Teluk Bone: Aktivitas Pelayaran dan Diaspora Bugis abad XVIII—XIX - Salim, Subarman; Subarman Salim (JURNAL JAWI, 2024)
This study aims to elucidate the maritime network of TelukBone from the 18th to the 19th century, with a focus on the formation of the network and the integration of regions within the Nusantara trade network. Historical methods and interviews with sailors, captains, and crew members were employed in this research. The results demonstrate the significant role of Bugis sailors as Nusantara diaspora. The Teluk Bone maritime network initially connected the southern and southeastern regions of Sulawesi, such as Kolaka, Boepinang, Pomala, and Buton, before expanding eastward to the Maluku Islands, Nusa Tenggara, Timor, Bali, and Papua. To the west, the network extended to Java, Kalimantan, Sumatra, the Riau Islands, and the Malay Peninsula. Bugis people's expertise in trade, inclusive thinking, and diplomatic skills played a crucial role in international trade in the Malacca Peninsula and Singapore. Their trading tactics and diplomatic prowess elevated the Bugis to the forefront of the Johor Kingdom's administration in the 18th century